Model Based Rotor Angle Fault Detection in PM Synchronous Machines - Hahn, Ingo; et al. (21st International Symposium on Power Electronics, Electrical Drives, Automation and Motion, 2012)
In safety-critical drive applications the knowledge of the rotor position of an electrical machine is essential to prevent damage of men and machines. This paper analyses several model-based rotor angle fault detection methods for permanent magnet synchronous machines (PMSM). Starting with a conventional fundamental wave machine model a method based on Analytical Redundancy Relations (ARR), a Parity Space approach, an observer structure and two simple back emf models are compared for fault detection. The ARR method is established with a graphical structural analysis and the Parity Space method is based on a Groebner basis approach. The observer method and the back emf models utilise conventional techniques. In an additional, part the machine model is extended with the differential mutual inductances to improve the dynamic fault detection characteristics. One back emf method is used to present the advantages of the extended machine model in contrast to the conventional one. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.modelb
Keywords: analytical redundancy relations; fault detection; parity space approach; permanent magnet synchronous machine